Monitoring Water Turbidity in a Temperate Floodplain Using UAV: Potential and Challenges. Issue 4 (4th July 2022) - Bussières, Savannah; Kinnard, Christophe; Clermont, Maxime; Campeau, Stéphane; Dubé-Richard, Daphney; Bordeleau, Pierre-André; Roy, Alexandre
Abstract: The Lake Saint-Pierre (LSP) is a wide (≈300 km 2 ) and shallow (≈3 m) lake created through a widening of the St. Lawrence River. Each spring, freshet makes it the largest floodplain in the province of Quebec. Agricultural practices in the littoral increase the water turbidity, which deteriorate the habitat's quality of many fish species. However, measuring spatio-temporal turbidity patterns in the LSP floodplain remain difficult because turbidity is highly variable in space and time. This study aims to evaluate the potential to use an Unmanned Aerial Vehicle (UAV) to measure the water turbidity in the LSP's floodplain. The results show that the UAV can efficiently measure the variation of turbidity in the LSP with a RMSE of 28.22 FNU. We also compared the turbidity retrieved from UAV with those retrieved from Sentinel-2 observations. The results show that the two models are comparable, even if Sentinel-2 yields better results. However, challenges remain when using UAV for turbidity monitoring, such as software limitations for mosaics creation over large water bodies. Nevertheless, the high spatial and temporal information can provide insights into the complex water turbidity patterns which characterize floodplains. The method could help land use management to improve the water quality of these ecosystems.